Seismic monitoring and vibrational characterization of small wind turbines: A case study of the potential effects on the Eskdalemuir International Monitoring System Station in Scotland. Issue 2 (1st October 2014) - Westwood, Rachel F.; Styles, Peter; Toon, Samuel M.
ABSTRACT: This paper presents a case study of the ground‐borne vibrations generated by small wind turbines. This is of particular importance for assessing the possible impact on the detection capabilities of the International Monitoring System seismic array at Eskdalemuir in Scotland. Measurements were gathered from a selection of small wind turbines (≤50 kW), from three different manufacturers, varying in hub height, power and construction using a range of accelerometers and seismometers fixed to the tower and buried in the adjacent ground at increasing distances. Previous studies have shown that medium and large turbines generate harmonic vibrations. Planning guidelines exist but have inadvertently led to a ban on the deployment of individual small‐turbines within 50 km of the array. This study investigates whether their inclusion in these guidelines is necessary. Vibration levels on the tower are in the region of 10 −3 m/sqrt(Hz), are transferred into the ground and decay rapidly away from the turbine (10 −5 m/sqrt(Hz) in the ground at 200 m). The spectral content of the vibrations shows variations between the turbines, but each have peaks in the band of interest for Eskdalemuir. Further, sources of the peaks in the spectra are identified as either originating from the blades' rotation or the resonant modes of the turbines. Analysis of the relationship between wind speed and seismic amplitude on the tower shows an exponential trend, individual to each wind turbine and the frequency band of interest. Similarly, analysis of the seismic amplitude between the tower and foundation shows that this can be described by a power law, but this is individual to each turbine. It is our opinion that there is little requirement to include turbines of 50 kW or less in planning guidelines outside the statutory exclusion zone of 10 km, but each turbine should be considered on an individual basis.